Primary ovarian mucinous adenocarcinoma of intestinal type: A clinicopathologic study of 46 cases - Surapan Khunamornpong (2018)
This study was aimed to evaluate the clinicopathologic details of primary ovarian mucinous adenocarcinoma and their prognostic significance. The clinicopathologic characteristics of 46 cases of mucinous adenocarcinoma were reviewed. The diagnosis of mucinous adenocarcinoma required the presence of stromal invasion of either the expansile (confluent glandular) pattern or the infiltrative pattern in an area size > 10 mm. The cases were stratified using different grading methods and different cutoff limits of stromal invasion. Regarding the invasive pattern, 20 cases had the infiltrative pattern only, 8 had both infiltrative and expansile patterns, 7 had the expansile pattern only, and 11 had the expansile pattern with infiltrative microinvasion (area ≤10 mm). The patients with tumors containing the expansile pattern had a younger mean age compared with those with the infiltrative pattern only (42.3 vs. 53.7 yr; P=0.004). On follow-up, 12 patients had tumor recurrence, 9 of whom died of disease. Tumor recurrence was associated with stage ≥II (P < 0.001) and infiltrative area > 10 mm (P=0.015). Decreased progression-free survival and cancer-specific survival was strongly associated with tumor stage ≥II (P < 0.001 for each survival) and infiltrative area > 50 mm (P=0.003 and 0.010, respectively). Among 27 stage IA patients, the infiltrative extent (area > 50 mm or dimension > 20 mm) was the only variable that was significantly associated with recurrence and decreased survival. Tumor grading was not significantly associated with the recurrence risk or the survival. The extent of infiltrative invasion in ovarian mucinous adenocarcinoma may provide additional prognostic value to the tumor stage and the pattern of stromal invasion. © 2014 International Society of Gynecological Pathologists.